Vstup do ekumenizmu. o. Roman Andrijovsʹkyj. Drohobyč = Introduction to Ecumenism by Rev. Roman Andriiovs’kii - Švecʹ, Roman (Bogoslovs'ki rozdymi, 2021)
Book review: Introduction to ecumenism. at. Roman Andriyovsky